Synthesis of Chondroitin Sulfate A Bearing Syndecan-1 Glycopeptide - Ramadan, Sherif (Org Lett, 2017)
Syndecan-1 chondroitin sulfate glycopeptide was synthesized for the first time using the cassette approach. The sequence of glycosylation to form the octasaccharide serine cassette was critical. The glycopeptide was successfully assembled via a 2+ (3 + 3) glycosylation strategy followed by peptide chain elongation.